Determinants of Employee Performance: The Role of Gender as a Moderator - Astuti, Rini Juni; Nurmalasari, Aldanti Aulia; Gunardi, Setiyawan Bin (Universitas Mercu Buana, 2025)
Objectives: The purpose of this study is to examine the role of gender as a moderator of employee performance improvement factors.Methodology: This research is quantitative research using a questionnaire survey method. The data obtained were 125 employees. The data obtained were tested using the Moderated Regression Analysis (MRA) model to obtain significant results.Finding: The results show that of the four factors studied, namely Knowledge Sharing Behavior, Organizational Learning, Transformational Leadership, and Workplace Spirituality, all factors can directly improve employee performance, but only Knowledge Sharing Behavior can be moderated by gender. The finding that Knowledge Sharing Behavior can be moderated by gender suggests that the way employees share knowledge in the workplace may differ based on gender, affecting performance outcomes. This could be due to several factors, such as differing communication styles, leadership dynamics, and societal expectations.Conclusion: The results show that only Knowledge Sharing Behavior can be moderated by gender, so this is a new finding to expand the research literature.